(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
The molecular mechanism behind the pharmacological action of a drug can be analyzed through In-silico studies, which utilize computational techniques to predict interactions, efficacy, and safety profiles. This study investigates the purgative action of Trivṛt (Operculina turpethum (L.) Silva Manso), a perennial twinner in the Convolvulaceae family, through molecular docking techniques and bioinformatics tools. Detailed in Āyurvedic texts, Trivṛt root is lauded for its efficacy in Virecana karma, a therapeutic approach for eliminating vitiated Pīṭha Doṣa. To identify bioactive phytocompounds from Trivṛt and their interactions with gastrointestinal motility receptors, comparing these with commercial laxatives through In-silico analysis. Findings indicate that the purgative effects are mediated by compounds such as Operculinosides D, Betulin, and Luteolin, which influence neurohumoral signals and smooth muscle contraction/relaxation via specific receptors. The results underscore the potential of Trivṛt root’s phytocompounds as viable therapeutic agents in gastrointestinal motility, paving the way for future drug discovery endeavors.